Electronic Spectral Characterization of Pr(III) Antibiotic Complexes in Solution - Jain, Renuka; Bhatnagar, Mridula; Dakshene, Monika (Asian Journal of Chemistry, 2010)
The present work involves the study of some Pr (III)-antibiotic complexes in 50 % DMSO-H2O composition. The ligands included five antibiotics (ceftizoxime, pipercillin, cefuroxime, cefotaxime and cefazolin). The effect of the ligand environment on electronic spectra of the metal ion with special reference to complexation and nature of metal-ligand bond has been investigated. Various energy parameters i.e., [Slate-Condon (Fk), Racah (Ek) and Lande parameter (z4f)], bonding parameter (b1/2), Nephelauxetic ratio (b)] and intensity parameters [oscillator strength (P), Judd-Ofelt parameter (Tl)] had been evaluated for different metal ligand stoichiometries.